Probiotic-rich fermented milk from Lactiplantibacillus plantarum IIA-1A5: Effects on pregnancy health in the animal model - Sukma, Ade; Suharto, El LS.; Melia, Sri; Juliyarsi, Indri; Vebriyanti, Ely; Fitria, Najmiatul; Rahmadian, Yudi; Hajrawati, Hajrawati; Arief, Irma I. (Narra J, 2024)
Previous studies of Lactiplantibacillus plantarum IIA-1A5 have shown its potential as a probiotic in modulating gut microbiota and providing health benefits; however, its effects during pregnancy remain underexplored. The aim of this study was to assess the safety of fermented milk enriched with L. plantarum IIA-IA5 in pregnant mice. An experimental study was conducted at Universitas Andalas, Padang, Indonesia. Two groups of pregnant mice (Mus musculus L.) were used, each with six mice. The control group received sterilized milk (10 mL/kg body weight (BW)), while the intervention group was given fermented milk containing L. plantarum IIA-1A5 (107 colony forming unit (CFU)/mL). The evaluated outcomes included maternal weight changes, fetal counts and measurements, and assessments of fetal morphology and skeletal development. Results indicated that the morphology of fetuses showed no significant differences between the control and intervention groups; both groups demonstrated normal development with no detected resorption sites, growth retardation, or hemorrhage. For skeletal development, both groups had the same bone counts, including frontal, parietal, intraparietal, exoccipital, supraoccipital, nasal, pre-maxilla, mandibular, thoracal, lumbar, sternum, and extremities. This study highlights that L. plantarum IIA-1A5-enriched fermented milk was safe, as no significant morphological or bone developmental abnormalities were observed, indicating its potential as a dietary supplement to support pregnancy health. However, further studies involving larger sample sizes may be needed to provide a more comprehensive assessment of its outcomes and safety.